Dispatch Riders, Eccleston Square, London, May 1926
1926-05-31 "Dispatch Riders, Eccleston Square, London, May 1926" [g0541001.jpg], May 1926 General Strike 1926. Dispatch riders wait for instructions outside TUC headquarters in Eccleston Square, London.